Hypopyon sign in dermatology (Revista de Medicina Clinica, 2024)
Clinical Snapshot on "Sign of Hypopyon in Dermatology" presented in Volume 8 Issue 2 of 2024 of Revista de Medicina Clínica.
Keywords: Blistering diseases; Bullous impetigo; Dermatology; Hypopyon sign; Pemphigus vulgaris